Clinical analysis of antibiotic encephalopathy in continuous ambulatory peritoneal dialysis patients(report of 10 cases) - JIANG Mei-hua; XU You-ping; HAN Zhi-wu; YAO Guo-qian; TAN Hong-mei; SHEN Jun; LI Jing; YANG Fang (Linchuang shenzangbing zazhi)
Objective To explore the clinical features and prevention of antibiotic encephalopathy in continuous ambulatory peritoneal dialysis(CAPD) patients.Methods Sixty-four CAPD patients using antibiotics were retrospectively studied from January 2008 to January 2014.Ten cases diagnosed as antibiotic encephalopathy served as observation group,and 15 cases out of the rest 54 nonantibiotic encephalopathy were randomly selected as control group.Significance was compared with ttest and x~2 test between two groups.Results The incidence of antibiotic encephalopathy was 15.6%.There was no significant difference in gender,plasma protein,electrolytes,and blood creatinine level between two groups(P>0.05).The patients were older,had more instances of cerebrovascular disease,and longer duration of dialysis and history of hemodialysis in observation group than in control group.The residual renal function was worse and peritoneal clearance was significantly lower in observation group than in control group.Beta-lactam was mainly used and the use time was over 3 days in observation group.Majority had good prognosis through complication prevention,and active treatment including adjustment of antibiotics and peritoneal dialysis prescription.Conclusions We should pay close attention to the management of older patients with cerebrovascular disease and avoid using the kind of antibiotics which easily entered blood-brain barrier and egested via the single channel.We should reasonably choose antibiotics based on residual renal function and detect adverse reaction,blood drug level,peritoneal clearance and pharmacokinetics feature.Patients once diagnosed as antibiotic encephalopathy were actively treated including adjustement of drug and peritoneal dialysis prescription.Hybrid renal replacement therapy was done if single dialysis was unsatisfactory.Hemoperfusion and hemodiafiltration were needed if the state of patients was severe.